Transcriptome pyrosequencing of the parasitoid wasp Cotesia vestalis: genes involved in the antennal odorant-sensory system. - Osamu Nishimura (Public Library of Science (PLoS), 2012)
Cotesia vestalis is an endoparasitic wasp that attacks larvae of the diamondback moth (Plutella xylostella), a herbivore of cruciferous plants. Females of C. vestalis use herbivore-induced plant odorants released from plants infested by P. xylostella as a host-searching cue. Transcriptome pyrosequencing was used to identify genes in the antennae of C. vestalis adult females coding for odorant receptors (ORs) and odorant binding proteins (OBPs) involved in insect olfactory perception. Quantitative gene expression analyses showed that a few OR and OBP genes were expressed exclusively in the antenna of C. vestalis adult females whereas most other classes of genes were expressed in the antennae of both males and females, indicating their diversity in importance for the olfactory sensory system. Together, transcriptome profiling of C. vestalis genes involved in the antennal odorant-sensory system helps in detecting genes involved in host- and food-search behaviors through infochemically-mediated interactions.